Security in Smart Cities: Models, Applications, and Challenges - Hassanien, Aboul Ella; Elhoseny, Mohamed; Ahmed, Syed Hassan; Singh, Amit Kumar (Lecture Notes in Intelligent Transportation and Infrastructure, 2019)
This book offers an essential guide to IoT Security, Smart Cities, IoT Applications, etc. In addition, it presents a structured introduction to the subject of destination marketing and an exhaustive review on the challenges of information security in smart and intelligent applications, especially for IoT and big data contexts. Highlighting the latest research on security in smart cities, it addresses essential models, applications, and challenges. Written in plain and straightforward language, the book offers a self-contained resource for readers with no prior background in the field. Primarily intended for students in Information Security and IoT applications (including smart cities systems and data heterogeneity), it will also greatly benefit academic researchers, IT professionals, policymakers and legislators. It is well suited as a reference book for both undergraduate and graduate courses on information security approaches, the Internet of Things, andreal-world intelligent applications. .